The inner exile of Leonor Serrano, Josefa Herrera and Angela Sempere, three female inspectors sanctioned by Primo de Rivera’s Dictatorship - Agulló Diaz, Maria del Carmen (Historia y Memoria de la Educación, 2022)
The repressive atmosphere and control exerted by the Dictatorship of Primo de Rivera over the primary education inspectorate included the promulgation of the R.O. of 19 April 1928, which mandated the forced transfer from their posts of seventeen of its members., These included the inspectors Leonor Serrano Pablo, Josefa Herrera Serra and Ángela Sempere Sanjuán, who were relocated as a form of punishment. In our search for the causes that led to these sanctions which remain unknown due to the lack of disciplinary procedures, we analyze their lives and professional trajectories. These suggest that the treatment given to these educators was conditioned by the gender variable, as they were linked to attitudes of disobedience to authorities’ orders, as well as to the manifestation of ideas considered dangerous, that is, related to women’s rights. Such attitudes were incompatible with the authoritarian principles of the regime and with its traditional view of women’s identity. Removed from their posts and uprooted from their cities of residence, the teachers were forced to resume their professional practices in an unfavourable environment, surviving their interior exile by combining an attitude of protest against their unjust situation with an intense professional activity tied to pedagogical innovation.